Question

In: Advanced Math

Solve y"+y=u(t-pi/2)+3 delta(t-3 pi/2)-u(t-2 pi), by laplace transform methods with y(0)=y'(0)=0.

Solve y"+y=u(t-pi/2)+3 delta(t-3 pi/2)-u(t-2 pi), by laplace transform methods with y(0)=y'(0)=0.

Solutions

Expert Solution


Related Solutions

Solve with Laplace transform 1. y''+ 4 t y'− 4y = 0, y(0) = 0, y'(0)...
Solve with Laplace transform 1. y''+ 4 t y'− 4y = 0, y(0) = 0, y'(0) = −7 2. (1− t) y''+ t y' − y = 0, y(0) = 3, y'(0) = −1
Solve the laplace transform to solve the initial value problem. y"-6y'+9y=t. Y(0)=0, y'(0)=1
Solve the laplace transform to solve the initial value problem. y"-6y'+9y=t. Y(0)=0, y'(0)=1
Solve the differential equation by Laplace transform y^(,,) (t)-2y^' (t)-3y(t)=sint   where y^' (0)=0 ,y=(0)=0
Solve the differential equation by Laplace transform y^(,,) (t)-2y^' (t)-3y(t)=sint   where y^' (0)=0 ,y=(0)=0
using the Laplace transform solve the IVP y'' +4y= 3sin(t) y(0) =1 , y'(0) = -...
using the Laplace transform solve the IVP y'' +4y= 3sin(t) y(0) =1 , y'(0) = - 1 , i am stuck on the partial fraction decomposition step. please explain the decomposition clearly.
Use the Laplace transform to solve the IVP: y^'''+y^''+3y^'-5y =16e^(-t); y(0)=0; y'(0)=2; y^'' (0)= -4
Use the Laplace transform to solve the IVP: y^'''+y^''+3y^'-5y =16e^(-t); y(0)=0; y'(0)=2; y^'' (0)= -4
Solve using the Laplace transform: y" + 4y = g(t) where y(0) = y'(0). Hint: Use...
Solve using the Laplace transform: y" + 4y = g(t) where y(0) = y'(0). Hint: Use the convolution theorem to write your answer. You may leave your answer expressed in terms of an integral.
Use Laplace transforms to solve: 3y’’ - 48y = (lowercase delta)(t - 2); y(0) = 1,...
Use Laplace transforms to solve: 3y’’ - 48y = (lowercase delta)(t - 2); y(0) = 1, y’(0) = -4
use laplace transform to solve the ivp y'' + 6y' + 45y = δ(t-6) y(0)=0, y'(0)=0...
use laplace transform to solve the ivp y'' + 6y' + 45y = δ(t-6) y(0)=0, y'(0)=0 y(t)=
Solve using laplace transform y" + 3y = -48t^2e^3t ; y(0) = 2 , y(0) =...
Solve using laplace transform y" + 3y = -48t^2e^3t ; y(0) = 2 , y(0) = 1 y" + 6y' + 5y = t - tu(t-2); y(0) = 1 , y'(0) = 0
Solve the differential equation using the Laplace transform.   y''' + 3y''+2y' = 100e-t , y(0) =...
Solve the differential equation using the Laplace transform.   y''' + 3y''+2y' = 100e-t , y(0) = 0, y'(0) = 0, y''(0) = 0
ADVERTISEMENT
ADVERTISEMENT
ADVERTISEMENT